1967
DOI: 10.1021/jf60153a010
|View full text |Cite
|
Sign up to set email alerts
|

Precursors of typical and atypical roasted peanut flavor

Abstract: Gross analysis of a soluble portion of raw peanuts before and after heating implicated amino acids

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
131
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(140 citation statements)
references
References 19 publications
9
131
0
Order By: Relevance
“…Some of these amino acids have been linked to the development of roasted peanut flavor. Aspartic acid, glutamic acid, asparagine, glutamine, histidine, andphe- nylalanine have been associated with 'typical' roasted peanut flavor (Newell et al, 1967). Arginine, threonine, tyrosine, and lysine have been linked to 'atypical' roasted peanut flavor (Newell et al, 1967;Cobb and Johnson, 1973).…”
Section: Tocopherolsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of these amino acids have been linked to the development of roasted peanut flavor. Aspartic acid, glutamic acid, asparagine, glutamine, histidine, andphe- nylalanine have been associated with 'typical' roasted peanut flavor (Newell et al, 1967). Arginine, threonine, tyrosine, and lysine have been linked to 'atypical' roasted peanut flavor (Newell et al, 1967;Cobb and Johnson, 1973).…”
Section: Tocopherolsmentioning
confidence: 99%
“…Arginine was lower in hirsuta samples and indicates an acceptable level of maturity . Free amino acids and free sugars are important precursors of roasted peanut flavor (Newell et al, 1967). The reactions be tween sugars and amino acids which influence peanut flavor are not well understood, but a study by Oupadissakoon and Young (1984) showed a strong posi tive correlation (r 2 = 0.928) between roasted peanut flavor and the amino acid and sugar content of raw seed.…”
Section: Tocopherolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Precursors of these compounds in peanuts are endogenous free sugars and free amino acids (Newell et al, 1967) which serve as sources of carbon and nitro gen for pyrazine formation. Although other seed compo nents such as lipids, phospholipids, and carbonyls (formed as a result of the Strecker degradation of amino acids) potentially contribute to the overall flavor of roasted peanuts (Johnson et al, 1971), the roasted flavor poten tial of any lot of raw peanuts may depend largely on the free amino acid and free sugar content in the seed.…”
mentioning
confidence: 99%